Causality and His Critical of the Western Concept - Roini, Winda; Sari, Arum; Mujahidah, Basmah (Proceedings of International Conference on Muslim Society and Thought, 2024)
Human thought patterns and perspectives are increasingly dominated by materialism and secularism. The universe is understood as something that has no beginning, is a mechanism, and is not related to the existence of God. As a figure who criticizes and rejects Western philosophical thought, al-Ghazali emphasized that the universe had a beginning and could not be separated from God’s role. This is certainly contrary to the Islamic worldview. This article aims to reveal al-Ghazali’s thoughts on the concept of causality, his criticism of Western thought, and his solutions to these problems. The method used in this research is qualitative with a content analysis approach. This research proves that al-Ghazali’s criticism of Western cosmology produces alternative solutions that are considered relevant to answering the problem of hegemonic thinking about materialism and secularism.